IMPROVING THE QUALITY OF FOOD AND DRINKING ENTREPRENEURS IN UNIVERSITY OF TRIBHUWANA TUNGGADEWI - Prihatminingtyas, Budi (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Quality is a dynamic condition associated with products, services, people who have or exceed expectations. UMKM can increase incomes in people who do not have a permanent job, then they are trying to find work that can generate money in accordance. The purpose of this research is 1. Explaining the Quality of product food and beverage entrepreneur in Tribhuwana Tunggadewi University. 2. Explaining the Quality of Human Resource UMKM food and beverages in the University Tribhuwana Tunggadewi Malang 3. Explaining the Quality of Service UMKM food and beverages in the University Tribhuwana Tunggadewi Malang. This research includes qualitative research, conducted in Tribhuwana Tunggadewi University for 5 months starting from March to August 2017. Data were obtained through interviews using questionnaires and secondary data obtained from related offices. The data were collected using census method, with 21 respondents. The results of this study is very useful to increase the repertoire of science. Based on the result of research, not only 3 variables are product quality, service quality, and quality of human resources influence income but there is one important variable is price of goods.